DESTRUCTIVE LESIONS OF BONES AS A RESULT OF MYCOBACTERIAL PROCESS IN CHILDREN WITH INITIAL IMMUNODEFICIENCIES (CLINICAL, DIAGNOSTICAL AND TACTIC PECULIARITIES) - A.Yu. Mushkin; E.V. Galkina; E.Yu. Malyarova; I.V. Kondratenko; K.N. Kovalenko; V.V. Vatutina ("Paediatrician" Publishers LLC, 2011)
Initial immunodeficiencies are genetically conditioned defects of immune system; they are the basis for generalized infections including those induced by mycobacteria of tuberculosis complex. The lesions of skeleton in those patients are of different types depending on the kind of immunodeficiency. The article presents the results of clinical observation, conservative and surgical treatment of 12 children with mycobacterial lesions of skeleton on the ground different initial immunodeficiencies - severe combined immune deficiency, chronic granulematosis and insufficiency of interferon and interleukin 12.Key words: children, initial immunodeficiency, mycobacterial infection, bone lesions, surgical treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 60-64)